Renewables firming using grid-scale battery storage in a real-time pricing market - Quann, Charles, author; Bradley, Thomas H., advisor; Petro, John, committee member; Valdes-Vasquez, Rodolfo, committee member (Colorado State University. Libraries, 2017)
Battery storage has many benefits, such as providing instantaneous response to changes in demand, clean electricity to customers, and integration of intermittent power sources. However, at the present time battery storage has proven to be too costly for widespread implementation. While there has been research to examine the cost at which battery storage will become cost effective for particular applications, little work has been done to determine the most effective placement of battery storage for the greatest impact on the system as a whole. This research examines battery storage in a real-time pricing energy market, and compares the cost effectiveness of three different cases: (1) Battery storage owned and operated by an intermittent renewable energy generation facility, (2) Battery storage connected to the grid providing energy services, (3) Battery storage owned and operated by a manufacturing plant. Real-time pricing data from ISO New England was analyzed to determine the monetary benefits of each case on a per mega-amp-hour basis. By looking at the issue holistically, instead of analyzing isolated scenarios, the benefits of each placement can be isolated from the overall benefits of connecting storage to the grid. Once the true value of each scenario can be accurately identified, the integration of utility scale battery storage is optimized to maximize benefits to all stakeholders. The results show that the economic benefit of a battery in a real-time pricing market is not dependent on the electrical generation or consumption attached to it. Instead, a grid-connected battery makes its own business case, meaning that existing battery storage can be leveraged for arbitrage and grid services without a loss of renewables firming capabilities.
Keywords: distributed power generation; real-time pricing; solar energy; energy storage; battery; renewable energy sources